Analisis Perilaku Hidup Bersih dan Sehat Siswa Madrasah Aliyah Babul Ulum Mariana - Dewi Sayati; Atma Deviliawati; Nani Sari Murni (Citra Delima Scientific journal of Citra Internasional Institute, 2025)
Schools are one of the settings that need to implement PHBS. The impacts that will arise if PHBS is not implemented in schools can be a decrease in achievement and enthusiasm for learning, a decrease in the image of the school, and an unconducive learning atmosphere due to a dirty environment and classroom conditions, unhealthy snacks, and unorganized waste disposal. These conditions will also cause various diseases. The purpose of this study was to analyze the clean and healthy living behavior of students at Madrasah Aliyah Babul Ulum. The research design used cross-sectional analysis. The population in this study were all students at Madrasah Aliyah Babul Ulum, totaling 82 people. The sample size in this study was the total population, namely 82 respondents. Bivariate analysis was carried out using the Pearson Correlation test, a confidence level of 95% and a significance limit with an ? value of 0.05. The results of the data analysis showed that CTPS had a p value of 0.018 on students' PHBS. Consuming healthy snacks in the school canteen p-value 0.147, free from cigarette smoke p-value 0.614, and disposing of garbage in its place p-value 0.199 on students' PHBS. The conclusion in the study showed a significant influence between the CTPS variable and Students' PHBS, but there was no influence between the variables of consuming healthy snacks in the school canteen, free from cigarette smoke, and disposing of garbage in its place with students' PHBS.